Gut endotoxin restriction prevents catabolic changes in glutamine metabolism after surgery in the bile duct-ligated rat. - Houdijk, A P (1997)
OBJECTIVE: The objective of this study was to investigate the role of gut-derived endotoxemia in postoperative glutamine (GLN) metabolism of bile duct-ligated rats. SUMMARY BACKGROUND DATA: Postoperative complications in patients with obstructive jaundice are associated with gut-derived endotoxemia. In experimental endotoxemia, catabolic changes in GLN metabolism have been reported. Glutamine balance is considered important in preventing postsurgical complications. METHODS: Male Wistar rats were treated orally with the endotoxin binder cholestyramine (n = 24, 150 mg/day) or saline (n = 24). On day 7, groups received a SHAM operation or a bile duct ligation (BDL). On day 21, all rats were subjected to a laparotomy followed 24 hours later by blood flow measurements and blood sampling. Glutamine organ handling was determined for the gut, liver, and one hindlimb. Intracellular GLN muscle concentrations were determined. RESULTS: Compared to the SHAM groups, BDL rats showed lower gut uptake of GLN (28%, p < 0.05); a reversal of liver GLN release to an uptake (p < 0.05); higher GLN release from the hindlimb (p < 0.05); and lower intracellular muscle GLN concentration (32%, p < 0.05). Cholestyramine treatment in BDL rats maintained GLN organ handling and muscle GLN concentrations at SHAM levels. CONCLUSIONS: Disturbances in postoperative GLN metabolism in BDL rats can be prevented by gut endotoxin restriction. Gut-derived endotoxemia after surgery in obstructive jaundice dictates GLN metabolism.